Flipped Problem-Based Learning on Basic Literacy and Self-Regulated Learning: A Systematic Literature Review - Ayi Ratnawati; Panca Dewi Purwati; Elliniawati Elliniawati (IJECA (International Journal of Education and Curriculum Application), 2025)
Educational transformation in the digital age requires adaptive learning approaches to develop students' basic literacy. This study aims to analyze the effect of Flipped Problem-Based Learning (FPBL) on basic literacy, explore the role of Self-Regulated Learning (SRL), and examine the interaction between the two in 21st-century learning. A Systematic Literature Review (SLR) based on PRISMA guidelines was conducted using Harzing’s Publish or Perish application, searching the Google Scholar and Scopus databases. Initially, 607 articles were identified. After screening for relevance and applying inclusion and exclusion criteria, 10 international articles were selected. These articles, published between 2020 and 2025 and indexed in Scopus, DOAJ, and SINTA, focused on FPBL, SRL, and basic literacy. The analysis reveals that FPBL positively impacts literacy, particularly in reading, numeracy, problem-solving, critical thinking, and digital literacy. SRL plays a central role in technology-based self-directed learning, where students with high self-regulation exhibit better literacy outcomes. The interaction between FPBL and SRL demonstrates a synergistic effect, further strengthening the development of basic literacy. In conclusion, this review emphasizes the significant contribution of FPBL to improving students’ basic literacy skills. It also highlights the vital role of SRL in optimizing self-directed learning and literacy outcomes. Combining FPBL with SRL strategies creates an adaptive, effective learning environment, essential for enhancing literacy in the digital age.